2008
DOI: 10.1111/j.1469-7580.2008.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial CD200 is heterogeneously distributed, regulated and involved in immune cell–endothelium interactions

Abstract: CD200 is a highly glycosylated cell surface protein containing two immunoglobulin superfamily domains in the extracellular region and performs immunosuppressive activities. It is widely distributed in various tissues including the vascular endothelium. We report here the distribution of CD200 in rat endothelia from different vascular beds. Endothelial CD200 immunoreactivity was weakly expressed in most arteries but was intensely expressed in the arterioles, most veins and venules, as well as continuous and fen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…6,28,29 Its role on blood vessel endothelium is not clear. 30 Ko and colleagues 30 suggested that endothe- lial CD200 may inhibit macrophage function, in part by downregulating macrophage adhesion molecules, to prevent aberrant diapedesis during inflammation. They found that in both mouse and human blood vessel endothelial cells, CD200 was differentially expressed and inducible depending on the type of endothelium.…”
Section: Commentmentioning
confidence: 99%
“…6,28,29 Its role on blood vessel endothelium is not clear. 30 Ko and colleagues 30 suggested that endothe- lial CD200 may inhibit macrophage function, in part by downregulating macrophage adhesion molecules, to prevent aberrant diapedesis during inflammation. They found that in both mouse and human blood vessel endothelial cells, CD200 was differentially expressed and inducible depending on the type of endothelium.…”
Section: Commentmentioning
confidence: 99%
“…Nevertheless, a large body of evidence has now been built which implicates a critical role for CD200:CD200R interactions in this process. Control of expression of CD200 at other sites, in this case on endothelial cells, is also reported to play a role in regulation of cell migration and adhesion of (T) lymphocytes in vascular beds, although not of macrophages in the same sites [69]. Endothelial CD200 expression was reported to be quite variable, with weak expression in most arteries and far greater expression in arterioles, veins, and venules, as well as on fenestrated capillaries.…”
Section: A Role For Cd200:cd200r In Regulation Of Immune Responsesmentioning
confidence: 95%
“…The levels of expression were altered following exposure to LPS, an effect entirely consistent with independent data using standard molecular tools, including chromatin immunoprecipitation (ChIP) assays with antibodies against NF-κB p65, STAT1, and IRF-1 which suggested that IFNγ and TNFα could induce CD200 expression through a 5 upstream enhancer and that NF-κB, STAT1, and IRF-1 played pivotal roles in this process [70,71]. The failure of macrophages to adhere may reflect, at least in part, an effect of CD200-triggered antagonism of CD200R1-facilitated adhesion [69].…”
Section: A Role For Cd200:cd200r In Regulation Of Immune Responsesmentioning
confidence: 99%
“…Distribution of CD200 in capillaries appears to be tissue-dependent and varies with the type of capillary; thus intense immunoreactivity is observed in continuous endothelia (both fenestrated and non-fenestrated) compared with relatively lower expression on discontinuous endothelia. Interestingly it has been shown that an anti-CD200 antibody blocked the adhesion of T cells to endothelial cells but did not affect the adhesion of macrophages; thus it was suggested that, whereas the primary role of the interaction between CD200 and its receptor may be to reduce activity of macrophages, a second role may be to modulate adhesion and migration of T cells into tissues (Ko et al, 2009). CD200 expression has also been examined on endothelial cells in the brain and it has been reported that expression in the hippocampus was evident only on the luminal surface of endothelial cells that made up the blood brain barrier (BBB), whereas in the area postrema, which lacks a BBB, clear staining was observed on the luminal and abluminal surfaces (Ko et al, 2009).…”
Section: Expression Of Cd200 and Its Receptormentioning
confidence: 99%
“…Interestingly it has been shown that an anti-CD200 antibody blocked the adhesion of T cells to endothelial cells but did not affect the adhesion of macrophages; thus it was suggested that, whereas the primary role of the interaction between CD200 and its receptor may be to reduce activity of macrophages, a second role may be to modulate adhesion and migration of T cells into tissues (Ko et al, 2009). CD200 expression has also been examined on endothelial cells in the brain and it has been reported that expression in the hippocampus was evident only on the luminal surface of endothelial cells that made up the blood brain barrier (BBB), whereas in the area postrema, which lacks a BBB, clear staining was observed on the luminal and abluminal surfaces (Ko et al, 2009). CD200 expression in brain tissue was found to be widespread with stronger staining in grey matter compared with white matter (Webb and Barclay, 1984).…”
Section: Expression Of Cd200 and Its Receptormentioning
confidence: 99%